JOB INVOLVEMENT DALAM PERSPEKTIF MANAJEMEN SUMBER DAYA MANUSIA: STUDI LITERATUR KUALITATIF - Widiyanti, Anik (JURNAL LENTERA BISNIS, 2026)
This study aims to examine the role of job involvement from a Human Resource Management (HRM) perspective and its implications for employee performance through a qualitative literature study approach. Job involvement is the level of an individual's psychological attachment to their work, reflected in self-identification, work meaning, and willingness to contribute optimally to the organization. In a dynamic work environment, job involvement becomes a strategic factor in increasing employee productivity and performance sustainability. The research method uses a qualitative literature study by reviewing national and international journal articles, scientific proceedings, and relevant academic books published in the last five years. Data were analyzed using content analysis and thematic synthesis techniques to identify patterns of relationships between HRM practices, job involvement, and employee performance. The results of the study indicate that job involvement plays a key role in bridging HRM practices with improved employee performance. Practices such as job design, training and development, and organizational support have been shown to increase job involvement, which impacts performance, organizational commitment, and innovative behavior. This study concludes that strengthening job involvement needs to be a primary organizational strategy in optimizing human resource management.